The new history of Korean civilization - Yu, Chai-Shin, 1932- (Bloomington, In : IUniverse, Inc, 2012)
This book "explores the existence of a distinctive Korean culture established by the Korean people and separate from its Chinese and Japanese counterparts. [The author] surveys the history of cultural life in Korea and provides a detailed account of this country's remarkable heritage ... Written for the purpose of introducing the roots of Korean culture to Westerners and second-generation Koreans living in the West."--P. [4] of cover.
Prehistoric culture of Korea -- Ancient society -- The middle ages of Korea -- The beginnings of early modern society -- Late Choso?n society -- Beginnings of modern society -- The development of modern society.
Keywords: Korea -- History; Korea -- Civilization